Separating yolk from white: A filter based on economic properties of trend and cycle - Peng Zhou (Cardiff University, Cardiff Business School, 2017)
This paper proposes a new filter technique to separate trend and cycle based on stylised economic properties of trend and cycle, rather than relying on ad hoc statistical proper-ties such as frequency. Given the theoretical separation between economic growth and business cycle literature, it is necessary to make the measures of trend and cycle match what the respective theories intend to explain. The proposed filter is applied to the long macroeconomic data collected by the Bank of England (1700-2015).
Keywords: C32; 330; Filter; Trend; Cycle